Studi Literature : Efektivitas Aromaterapi terhadap Kecemasan dan Kualitas Tidur pada Ibu Hamil - Tri Restu Handayani; Ummy Khairussyifa (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Background: Pregnancy is a physiological process experienced by every woman, but it can be accompanied by various discomforts, both physical and psychological. In the third trimester, hormonal, physical, and emotional changes often trigger complaints such as anxiety, difficulty sleeping, and discomfort. These conditions, if not managed, can negatively impact the health of the mother and fetus, including increasing the risk of pregnancy complications. One non-pharmacological approach that is increasingly in demand to address these problems is aromatherapy, namely the use of essential oils from plants as a complementary therapy. Objective: This literature study aims to explore the effectiveness of aromatherapy in reducing anxiety levels and improving sleep quality in pregnant women, especially in the final trimester. Methods: A narrative literature review was conducted by analyzing ten national journal articles published between 2014–2024. Articles were selected through a purposive sampling method based on the suitability of the topics with aromatherapy, pregnancy, anxiety, and sleep quality. Results: Most studies show that aromatherapy, especially with lavender, orange, and chamomile essential oils, has a positive effect in reducing anxiety levels and improving sleep quality. The mechanism of action of aromatherapy is thought to involve stimulation of the limbic system in the brain via the olfactory pathway, which plays a role in regulating emotions, inducing relaxation, and reducing sympathetic nervous system activity. These effects help reduce tension and facilitate better sleep in pregnant women. Conclusion: Aromatherapy has been shown to be a safe, easy-to-implement, and effective complementary intervention for addressing anxiety and sleep disturbances in pregnancy. Healthcare providers, particularly midwives, are advised to integrate this therapy into holistic antenatal care to support the overall well-being of pregnant women.